Independent at heart: persistent association of altitude with ischaemic heart disease mortality after consideration of climate, topography and built environment. Issue 8 (20th January 2016) - Faeh, David; Moser, André; Panczak, Radoslaw; Bopp, Matthias; Röösli, Martin; Spoerri, Adrian; ,
Abstract : Background: Living at higher altitude was dose-dependently associated with lower risk of ischaemic heart disease (IHD). Higher altitudes have different climatic, topographic and built environment properties than lowland regions. It is unclear whether these environmental factors mediate/confound the association between altitude and IHD. We examined how much of the altitude-IHD association is explained by variations in exposure at place of residence to sunshine, temperature, precipitation, aspect, slope and distance to main road. Methods: We included 4.2 million individuals aged 40–84 at baseline living in Switzerland at altitudes 195–2971 m above sea level (ie, full range of residence), providing 77 127 IHD deaths. Mortality data 2000–2008, sociodemographic/economic information and coordinates of residence were obtained from the Swiss National Cohort, a longitudinal, census-based record linkage study. Environment information was modelled to residence level using Weibull regression models. Results: In the model not adjusted for other environmental factors, IHD mortality linearly decreased with increasing altitude resulting in a lower risk (HR, 95% CI 0.67, 0.60 to 0.74) for those living >1500 m (vs<600 m). This association remained after adjustment for all other environmental factors 0.74 (0.66 to 0.82). Conclusions: The benefit of living at higher altitude was only partially confounded by variations in climate, topography and built environment. Rather, physical environment factors appear to have an independent effect and may impact on cardiovascular health in a cumulative way. Inclusion of additional modifiable factors as well as individual information on traditional IHD risk factors in our combined environmental model could help to identify strategies for the reduction of inequalities in IHD mortality.